STRATEGI MEMPERTAHANKAN NILAI-NILAI PESANTREN SALAF DI ERA MODERN - Ahmad Badrus Sholeh (Mozaic: Islamic Studies Journal, 2022)
This research is motivated by the increasing number of violence and intolerance in Indonesia as well as the need for attitudes of salaf Islamic boarding schools that can explain how individuals can live in harmony in diversity and achieve a peaceful life. This study aims to determine the strategies for surviving salaf values ​​in the Salafiyah Islamic boarding school Curah kates Klompangan and Darul Kasyfil Ulum Karangsono Jember Islamic boarding school, the similarities and differences in the two research locations will be points that show the uniqueness and uniqueness of each pesantren. The uniqueness and distinctiveness that comes from local wisdom will further employ scientific treasures, especially those related to salaf culture. This study uses in-depth interviews, observations and uses documentation in the data mining process, and analyzes it with integrative analysis techniques that combine and use formulations from a combination of several relevant salaf cultural value theories. The results described in this study are the strategy of defending the values ​​of the salaf strategy which aims to maintain on a micro scale. On a micro scale, this salaf attitude will have an impact on national attitudes that can accept differences in many ways as fellow citizens.